A Linguistic Analysis of Zimbabwean Prime Minister Morgan Tsvangiraias Image Repair Discourse: Letter to the Zimbabwean Public (30 November 2011) (Global Journal of Human-Social Science, 2013)
The reputations of politicians as well as other popular figures depend on public perceptions and once reputations are threatened, images repair becomes vital. This paper focuses on the image repair strategies used in the public letter of apology (30 November 2011) by Prime Minister Morgan Tsvangirai released shortly after divorcing his wife Lorcadia Karimatsenga. The major concern is to determine the effectiveness of the communication devices used in redeeming the PM's image in the public eye. Benoit's Image Repair Theory (1995) is used as theoretical guide and methodological impetus of the study. Benoit theory provides a mechanism for analyzing the communication strategies used. Five major impression management strategies are adopted: denial, evasion of responsibility, reducing the offensiveness of the event, corrective action and mortification. It is concluded in this study that despite the mistake of omitting some important details that could have assisted in clearing his name, the image repair strategies used by Tsvangirai were to a large extent effective.